Penguatan Critical Thinking Santri Melalui Teknik Muhadharah Di Pondok Pesantren - Junaedi Sitika, Achmad; Sahrurrpmadhon, hikmatiyar; Nurhasanah (Universitas Majalengka, 2025)
Muhadharah carried out at the Khairul Bariyyah Islamic Boarding School in Bekasi City can develop and strengthen the critical thinking abilities of students as in the thesis title above, namely